Away we go. (New York : Grosset & Dunlap, 2004)
A collection of classic Dick and Jane stories in which they play with Sally, Tim, Spot, and Puff, and take a trip with their parents.
Keywords: Readers (Primary); Readers -- Juvenile fiction